2020
DOI: 10.1021/acs.chemmater.0c02919
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Contactable and Antifreezing Strain Sensors Based on Bilayer Hydrogels

Abstract: Currently, most hydrogel sensors require an isolation layer to prevent the current from damaging the skin. However, the mismatch of the mechanical property between the isolation layer and the hydrogel sensor may affect the accuracy of the sensing. Herein, a bilayer hydrogel sensor consisted of a nonconductive layer and a conductive layer, which were prepared through twice freeze–thawing methods. The nonconductive layer which could directly come in contact with the skin was composed of polyvinyl alcohol (PVA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 59 publications
0
69
0
Order By: Relevance
“…25–27 Moreover, the strains of the adhesive layer and tough layer are different under the same stress, which will affect the sensitivity of the hydrogel strain sensor. 28 Compared with a bilayer structure, a gradient structure can avoid these problems. 29 Mooney et al reported gradient adhesive–tough hydrogels by introducing chitosan and other polymers into polyacrylamide/alginate–calcium tough hydrogels to form a positively charged adhesive surface (about 40 μm depth).…”
Section: Introductionmentioning
confidence: 99%
“…25–27 Moreover, the strains of the adhesive layer and tough layer are different under the same stress, which will affect the sensitivity of the hydrogel strain sensor. 28 Compared with a bilayer structure, a gradient structure can avoid these problems. 29 Mooney et al reported gradient adhesive–tough hydrogels by introducing chitosan and other polymers into polyacrylamide/alginate–calcium tough hydrogels to form a positively charged adhesive surface (about 40 μm depth).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we need to find a balance between conductivity and mechanical properties by tuning the ratio of HEDP according to specific application requirements. We further compared our results with previous studies that demonstrate hydrogels with excellent mechanical toughness or conductivity [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], as shown in Figure 2 e,f. It is also worth mentioning that our PVA-HEDP hydrogels exhibited excellent conductivity and mechanical performance simultaneously.…”
Section: Resultsmentioning
confidence: 73%
“…( d ) Compressive stress–strain curves of the hydrogels with various HEDP contents. ( e , f ) Comparison of electrical and mechanical properties with previous research work [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Figurementioning
confidence: 92%
“…Delocalized 𝜋-electrons act as charge carriers moving freely along the unsaturated backbone. Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), [31,33,34] polyaniline (PANi), [69,70] and polypyrrole (Ppy) [35] are typical conjugated conductive polymers, with conductivities comparable to those of semiconductors and metals. Conventional conjugated conductive polymers with modulus in order of 1 GPa are not much stretchy, thus, mechanically mismatch skin.…”
Section: Conjugated Conductive Polymer Gelsmentioning
confidence: 99%